Relationship between Organizational Learning Culture and Customer Satisfaction in Nepalese Insurance Industry - Yadav, Punita (Nepalese Journal of Management, 2025)
This study examines the relationship between organizational learning culture and customer satisfaction in the Nepalese insurance industry. Customer satisfaction is the dependent variable. The selected independent variables are training and development programs, knowledge sharing mechanism, openness to new ideas and innovation, communication and feedback process, leadership support for learning and improvement, and employee engagement in learning activities. The primary sources of data are used to assess the opinions of respondents regarding training and development programs, knowledge sharing mechanism, openness to new ideas and innovation, communication and feedback process, leadership support for learning and improvement, employee engagement in learning activities and customer satisfaction. The study is based on the primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of relationship between organizational learning culture and customer satisfaction in the Nepalese insurance industry. The study showed a positive impact of training and development program on customer satisfaction. It indicates that training and development program provided by insurance industry leads to increase in customer satisfaction. Similarly, the study showed a positive impact of knowledge sharing mechanism on customer satisfaction. It indicates that adoption of knowledge sharing mechanism leads to increase in customer satisfaction. Likewise, the study showed a positive impact of communication and feedback process on customer satisfaction. It indicates that practices of communication and feedback process leads to increase in customer satisfaction. Further, the study showed a positive impact of openness to new ideas and innovation on customer satisfaction. It indicates that practices of openness to new ideas and innovation leads to increase in customer satisfaction. In addition, the study also showed a positive impact of leadership support for learning and improvement on customer satisfaction. It indicates that activities of learning and improvement leads to increase in customer satisfaction. Similarly, the study showed a positive impact of employee engagement in learning activities on customer satisfaction. It indicates that practices of engagement in learning activities leads to increase in customer satisfaction.